Does upper-body compression improve 3 × 3-min double-poling sprint performance? - Sperlich, B.; Born, D.-P.; Zinner, C.; Hauser, A.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To evaluate whether upper-body compression affects power output and selected metabolic, cardiorespiratory, hemodynamic, and perceptual responses during three 3-min sessions of double-poling (DP) sprint. Method: Ten well-trained male athletes (25 ± 4 y, 180 ± 4 cm, 74.6 ± 3.2 kg) performed such sprints on a DP ski ergometer with and without a long-sleeved compression garment. Result: Mean power output was not affected by such compression (216 ± 25 W in both cases; P = 1.00, effect size [ES] = 0.00), although blood lactate concentration was lowered (P < .05, ES = 0.50-1.02). Blood gases (ES = 0.07-0.50), oxygen uptake (ES = 0.04-0.28), production of carbon dioxide (ES = 0.01-0.46), heart rate (ES = 0.00-0.21), stroke volume (ES = 0.33-0.81), and cardiac output (ES = 0.20-0.91) were also all unaffected by upper-body compression (best P = 1.00). This was also the case for changes in the tissue saturation index (ES = 0.45-1.17) and total blood content of hemoglobin (ES = 0.09-0.85), as well as ratings of perceived exertion (ES = 0.15-0.88; best P = .96). Conclusion: The authors conclude that the performance of well-trained athletes during 3 × 3-min DP sprints will not be enhanced by upper-body compression.